2012
DOI: 10.18378/rvads.v7i3.1338
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de solubilização de fosfato e produção de AIA por Trichoderma spp.

Abstract: O presente trabalho teve como objetivo avaliar o potencial de produção de ácido indol acético (AIA) e a capacidade de solubilização de fosfato, in vitro, por isolados de Trichoderma spp. A partir de colônias de Trichoderma crescidas em meio BDA (batata, dextrose e Agar), foram retirados discos de aproximadamente 8,0 mm de diâmetro, contendo micélio e esporos e repicados para Erlenmeyer (250 mL) contendo meios BD (batata e dextrose) e FAN (glicose e extrato de levedura) na ausência e presença de L-triptofano, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Trichoderma strains can provide plants with nutrients and phytohormones, such as the production of indoleacetic acid (IAA), gibberellic acid, and ethylene hormones that influence carbohydrate metabolism and photosynthesis (Contreras-Cornejo et al, 2016;Chagas et al, 2017b). Oliveira et al (2012) also highlight that growth promotion shows a correlation between biomass and hormone production, as well as that these microorganisms provide the plant with nutrients, such as phosphorus, which is vital for plant development and production. Among the mechanisms involved in growth promotion of seedlings inoculated with Trichoderma, the production of volatile and non-volatile metabolites by these fungi might stimulate plant physiology in cell multiplication (Patil et al, 2016;Ramada et al, 2019;Bononi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma strains can provide plants with nutrients and phytohormones, such as the production of indoleacetic acid (IAA), gibberellic acid, and ethylene hormones that influence carbohydrate metabolism and photosynthesis (Contreras-Cornejo et al, 2016;Chagas et al, 2017b). Oliveira et al (2012) also highlight that growth promotion shows a correlation between biomass and hormone production, as well as that these microorganisms provide the plant with nutrients, such as phosphorus, which is vital for plant development and production. Among the mechanisms involved in growth promotion of seedlings inoculated with Trichoderma, the production of volatile and non-volatile metabolites by these fungi might stimulate plant physiology in cell multiplication (Patil et al, 2016;Ramada et al, 2019;Bononi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…isolates tested byOliveira et al (2012) also produced IAA, and the use of the L-tryptophan precursor had a positive effect of inducing the synthesis of this phytohormone Badawi et al (2011). studied species of Trichoderma harzianum and reported their capacity to produce this phytohormone, thus promoting plant growth Chowdappa et al (2013).…”
mentioning
confidence: 99%
“…Using 14 Trichoderma stems extracted from the rhizosphere of forest trees such as Pinus roxburghii, Cedrus Deodara, Bambusa bambos, Psidium guajava and Quercus sp, tested in vitro and in a greenhouse with chickpeas (Cicer arietinum L.), Kapri and Tewari ( 2010) Trichoderma isolates are capable of promoting plant growth by synthesizing the hormone indoleacetic acid (IAA) (GRAVEL et al, 2007;OLIVEIRA et al, 2012). Evaluating the production of secondary metabolites in 101 Trichoderma isolates, Hoyos-Carvajal et al (2009) found that 60% of the strains were able to produce AIA or similar to auxin.…”
Section: Myracrodruon Urundeuva Fr All Without Fertilizationmentioning
confidence: 99%
“…é um importante agente de controle biológico, uma vez que, reduzem a presença de fitopatógenos no agroecossistema (MELLO et al, 2020;SOOD et al, 2020). Além disso, estes fungos apresentam papel relevante na promoção de crescimento das plantas hospedeiras, não apenas pela eficiência como agente de controle biológico, mas também porque a endosimbiose pode otimizar a absorção de nutrientes, solubilizar fosfatos, produzir fitohormônios como a auxina, produzir sideróforos e promover o aumento da resistência a salinização (OLIVEIRA et al, 2012;SARAVANAKUMAR et al, 2013;CONTRERAS-CORNEJO et al, 2014, SOOD et al, 2020.…”
Section: Introductionunclassified